2010
DOI: 10.1182/blood-2009-06-227298
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation and IL-15 promote loss of CD8 T-cell tolerance in response to lymphopenia

Abstract: Functional inactivation of self-reactive T lymphocytes contributes to the maintenance of immunologic self-tolerance. At the same time, tolerance induction limits immune responses against tumors expressing tolerizing self-antigens. Some cancer therapies include the adoptive transfer of tumor-reactive T lymphocytes into lymphopenic patients. Lymphopenia provides an activation signal to T lymphocytes, which undergo lymphopeniainduced proliferation (LIP), acquire effector functions, and reject tumors. However, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Such changes may result from the competition between cells supporting the response of each system and may be related to critical cytokines and growth factors. For example, interleukin 15 is tightly regulated 82 and important for vascular remodeling at the maternal fetal interface 83 for CD8 T-cell homeostasis 84,85 and for tissue-resident T-cell development. 86 Based on these findings herein, and others, 37,50 we speculate that unique interaction between immune and vascular systems is set by the experience of pregnancy and placenta-related factors 87 and continues in PP.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes may result from the competition between cells supporting the response of each system and may be related to critical cytokines and growth factors. For example, interleukin 15 is tightly regulated 82 and important for vascular remodeling at the maternal fetal interface 83 for CD8 T-cell homeostasis 84,85 and for tissue-resident T-cell development. 86 Based on these findings herein, and others, 37,50 we speculate that unique interaction between immune and vascular systems is set by the experience of pregnancy and placenta-related factors 87 and continues in PP.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in a macaque model where autologous CMV-specific CD8 + T cell clones generated in the presence of IL-15 acquired a central-memory phenotype rather than terminally differentiated effector phenotype and displayed superior persistence (15). Additional findings also demonstrated a role of IL-15 in breaking tolerance and in rescuing tolerant CD8 + T cells for use in adoptive immunotherapy of established tumors (16,17) and in augmenting antigen-specific CD8 + T cells response upon vaccination (18). …”
Section: Introductionmentioning
confidence: 89%
“…All these observations lead us and others to hypothesize that lymphodepletion perturbs the establishment of tolerance. Indeed, it has been recently shown that lymphodepletion promotes the breakdown of peripheral CD8 + T cell tolerance [29, 30]. In this report, we examined the role of systemic LPS translocation in the breakdown of CD8 + T cell cross-tolerance as it occurs in sublethally irradiated InsHA mice.…”
Section: Discussionmentioning
confidence: 96%
“…However, many different cell populations are still activated in antibiotic treated mice and would be able to produce cytokines at later time points after irradiation. Indeed, the increased availability of cytokines other than IL-7 observed in irradiated mice has been shown to contribute to the gain of effector functions by T cells [30, 57]. Finally, the removal of suppressive populations involved in maintaining T cells under control [15, 57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation